PENGARUH PEMBERIAN PROPOLIS TERHADAP EKSPRESI BDNF DI HIPPOCAMPUS TIKUS YANG DIINDUKSI STRES - Kuswati Kuswati; Zainuri Sabta Nugraha; Ety Sari Handayani (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2021)
Background: Brain-derived neurotrophic factor (BDNF) is a neurotrophin secreted by dendrite, which plays a role in differentiation, maturation, neuroplasticity, learning, and memory, which the expression decreases under stress conditions. Propolis contains chrysin which has antioxidant and neuroprotectant effects.Objective: This study aimed to examine the effect of propolis on BDNF expression in the hippocampus of stress-induced rats.Methods: Experimental study using posttest only control group design. The subjects were 25 male Spraque-Dawley rats (Rattus norvegicus), four months old, weighing 200-300 grams. Rats were randomly divided into five groups: group N, did not receive any treatment; group K, received stress treatment; groups P1, P2, and P3, received stress treatment and followed by administered propolis at doses of 100, 150, and 200 mg/kg/day. Social isolation stress was carried out by putting one rat in one cage. Oral propolis administration used oral gavage. In the end, the rats were terminated and brain tissue was collected. Immunohistochemical staining using anti-BDNF antibodies was performed to make histological slides. Observations were made with a light microscope with 1000x magnification in the CA1 area of the hippocampus.Results: There is a significant difference in BDNF expression in the CA1 area of the hippocampus in all groups (p=0.000). The highest BDNF expression was in the P3 group and the lowest in group K.Conclusion: There is an effect of propolis on BDNF expression in the hippocampus of the stress-induced rat. Propolis dose of 100 mg/kgBW/day has increased BDNF expression.